"They Make Heavy Stuff Lighter." Youth Workers in the Hospital Setting: A Service Evaluation. Issue 1 (2nd January 2023) - Marshall, Marie; Waring, Gillian
ABSTRACT: This article presents the findings of a service evaluation on the role of the youth worker offered to young people in the hospital setting across the United Kingdom and what differentiates the role of the youth worker from other health-care professionals, as described by young people, parents, and members of the existing multidisciplinary team. Young people, parents, and members of multidisciplinary teams were approached by a youth worker in the hospital regarding the purpose of the evaluation and the online survey relating to their views and experiences of working with a youth worker in the hospital setting. Data were analyzed descriptively. The n value represents the total number of responses: Young people 11–25 years ( n = 47), mothers/fathers ( n = 16), and members of the multidisciplinary team ( n = 76). The findings suggested that the youth worker was highly valued by all, with a consensus that they had a positive impact on the experiences of young people, their parents, and members of the multidisciplinary teams. Youth workers were reported as offering a more relatable style of engagement that connected with young people on a different and more informal level than other members of the multidisciplinary team. Their approach to the support provided was also different as their focus was guided by what young people valued. Youth workers acted as the bridge between young people, their parents, and the multidisciplinary team and were considered by the multidisciplinary teams to be a fundamental ingredient when working with young people in the hospital setting. The findings from this evaluation provide unique insights into the role the youth worker offers to young people in hospital settings that is different from what other health-care professionals provide, as reported by young people, parents, and the multidisciplinary team. However, further evaluation of the service should include objective outcome measures of the role and in-depth qualitative research to gain a greater and more detailed understanding of young peoples', parents', and members of the multidisciplinary team's views and experiences of what makes this role different.